PENGARUH PENGEMBANGAN KARIR DAN KOMITMEN ORGANISASIONAL TERHADAP SEMANGAT KERJA PADA RSUD SELATPANJANG - Iswanti, Selpiya Okta; Karneli, Okta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research was conducted at Selatpanjang Hospital which is located on Jalan Dorak Selatpanjang. The purpose of the study was to determine and analyze the effect of career development and organizational commitment on morale partially and simultaneously. The research method used is descriptive quantitative analysis obtained from the results of questionnaires distributed to 117 respondents to non-medical employees of RSUD Selatpanjang, which is then processed with the SPSS program by conducting validity tests, reliability tests, simple linear regression analysis, multiple linear analysis, analysis of determination (R2) and test the hypothesis by testing t (partial) and F (simultaneous). The tests conducted showed that career development had a positive and significant effect on morale, organizational commitment had a positive and significant effect on morale, then career development and organizational commitment had a positive and significant effect on morale in non-medical employees of RSUD Selatpanjang. Keywords: Career Development, Organizational Commitment, Morale